Relationships between three and twelve month outcomes in children enrolled in the therapeutic hypothermia after pediatric cardiac arrest trials. (June 2019) - Slomine, Beth S.; Silverstein, Faye S.; Page, Kent; Holubkov, Richard; Christensen, James R.; Dean, J. Michael; Moler, Frank W.; ,
Abstract: Aim: To inform design aspects of future trials by comparing 3 and 12-month neurobehavioural outcomes in children enrolled in Therapeutic Hypothermia After Pediatric Cardiac Arrest Out-Of-Hospital and In-Hospital (THAPCA-OH, THAPCA-IH) trials. Methods: The THAPCA trials evaluated two targeted temperature management interventions (hypothermia, 32.0–34.0 °C; normothermia, 36.0–37.5 °C). Children, aged 2 days to <18 years, were enrolled from 2009–2015. Three and 12-month post-cardiac arrest (CA) outcomes included the Vineland Adaptive Behavior Scales, Second Edition (VABS-II) (population mean = 100, SD = 15) and the pediatric cerebral performance category (PCPC) scale. Children without significant pre-existing neurodevelopmental deficits were included in primary outcome analyses. Among survivors, favorable 12-month outcome was defined as VABS-II ≥ 70. Results: VABS-II and PCPC were available at 3 and 12 months in 204 of 222 eligible survivors (THAPCA-OH, n = 82; THAPCA-IH, n = 122). Relative to THAPCA-IH, THAPCA-OH had significantly less pre-CA disability and significantly greater 12-month CA impairment, based on both VABS-II and PCPC. Correlations between 3 and 12-month VABS-II scores were strong for THAPCA-OH (r = 0.95) and THAPCA-IH (r = 0.72), and lower (p ≤ 0.001) in THAPCA-IH. Between time-points correlations were lower, but still significant in children <1 year at CA (p < 0.001). In both cohorts, 3-month VABS-II and PCPC categorical outcomes had high sensitivity (≥70%) for predicting favorable 12-month VABS-II outcomes, but specificity was lower for THAPCA-IH (68–89%) relative to THAPCA-OH (≥95%). Overall, 12-month diagnostic accuracy was ≥80% for both VABS-II and PCPC in both cohorts. Conclusions: In future paediatric cardiac arrest clinical trials that enroll similar cohorts, integration of 3-month neurobehavioral outcome measures should be considered.